Pengaruh Citra Merek Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Polis Asuransi Manulife Financial Cabang Bogor - Fadillah, Adil; Meinar, Ratna (Jurnal Ilmiah Manajemen Kesatuan, 2016)
Brand image is one of the most important parts of a product. Brand image could be an added value for the company's products because it means the brand leaves a certain meaning to be memorized by the consumers. A brand image also hase meanings, forms and means different things to each of its peers. Success in building a strong brand will be created if the elements of the marketing strategy can be met, especially in terms of quality of service marketing. Quality customer service is important so that companies can continue to survive in the competition. Sales marketing is the cornerstone of the company's key to the success of the company. If the company wants to go forward, it should be able to create a powerful marketing force, resourceful and able to compete with the sales of other companies.Influence of brand image and quality of service Manulife Financial insurance policy against the customer's purchase decision explained by the multiple regression model Y = 3.317 + 0.406 X1 + 0.406 X2. The regression model explained that if the influence of brand image variables and quality of service were ignored, the average customer purchase decision variable is estimated at 3,315. If it is not affected by the variable quality of service, then the average customer purchase decision variable is estimated to reach 3.723 for each increase of 1 unit of brand image variables. If it is not influenced by brand image variables alone, the average customer purchase decision variables with each estimated to reach 3.723 for every 1 unit increase in the variable quality of service. Brand image variables and quality of service simultaneously gives the total effect of 73.4% based on the coefficient of determination. Other variables not included in this study effect of 26.6%. Evaluation results from these studies show that the measures undertaken by the insurance company Manulife Financial is to discovery good brand image and provide quality service, such measures will create an insurance policy purchase decision process.